Social Learning Theory: Cognitive and Behavioral Approaches - Deri Firmansyah; Dadang Saepuloh (PT FORMOSA CENDEKIA GLOBAL, 2022)
Social learning theory (SLT) and social cognitive theory (SCT), identify learning as a dynamic interaction between people, environment, and behavior. Engagement in a social context involves a dual process of making meaning. This study focuses on the concepts of SLT and SCL theorized by Albert Bandura, complemented by other relevant literature. Behavioral theory begins with studying the theory of behaviorism postulated by Skinner, supplemented by some other relevant literature afterwards. To meet this objective, three stages of systematic literature review were adapted and developed, namely planning, implementation, and reporting. Also a database search with a snow ball approach was chosen, in order to complete the lack of necessary information and data. These stages serve as a framework for the operationalization of this article, data extraction and synthesis, discussion of the findings of the study are described, ending with presenting conclusions and recommendations.